1+9m=-62

Simple and best practice solution for 1+9m=-62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+9m=-62 equation:


Simplifying
1 + 9m = -62

Solving
1 + 9m = -62

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 9m = -62 + -1

Combine like terms: 1 + -1 = 0
0 + 9m = -62 + -1
9m = -62 + -1

Combine like terms: -62 + -1 = -63
9m = -63

Divide each side by '9'.
m = -7

Simplifying
m = -7

See similar equations:

| 5y+13=113 | | 6x+7-2x-14=4x+8 | | 21-8z=-11 | | 216=w(w+6) | | 9(3n+3)=7(7n+7)+7 | | 2(x-4)=-12(3x+1) | | 2(0.5-y)=4.6 | | 7x-5(3x-7)=11 | | x^2=3n | | (7x-16)+(x+8)+(4x)=180 | | 13x+2y=10 | | 12(3)(-2)= | | 8-2h=58 | | 5y+2x=60 | | 3(x+6)+3=3+5(x-4) | | 4p^2+12p+3=0 | | 8e+4-(3+9e)= | | 6.2a+10=72 | | 2m+4m=m | | (12x^2)-8x=0 | | 6x(-12)= | | 5(x+16)=x-8 | | 6(x-1)=16 | | 2x+5x-6=9x-8 | | 2x+4(x-8)=-52 | | 143-4x=5x-136 | | 9.06x+63.42=126.84 | | ln(7x+20)=ln(4x-4) | | (x)=1/2(X) | | 9.06+63.42=126.84 | | 2/5*2/5= | | 7x=2+15y |

Equations solver categories